1995
DOI: 10.1097/00000658-199504000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate Comparison of Complications After Laparoscopic Cholecystectomy and Open Cholecystectomy

Abstract: ObjectiveTo answer the question whether laparoscopic cholecystectomy (LC) or open cholecystectomy (OC) is safer in terms of complications, the authors evaluated complications relating to 1440 cholecystectomies performed by the same surgeons in a retrospective study. Summary Background DataA definite pronouncement on whether LC truly is superior to OC is not possible because prospective trials are burdened with problems of recruitment. MethodsAfter the introduction of LC at the authors' institution in April 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
69
0
5

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(78 citation statements)
references
References 17 publications
4
69
0
5
Order By: Relevance
“…Laparoscopic cholecystectomy (LC) has become the gold standard for the surgical treatment of benign gallbladder diseases owing to its shorter hospitalization, more rapid recovery, and much fewer wound complications when compared to open cholecystectomy (1)(2)(3)(4). However, a direct vision is essential for safe dissection of Calot's triangle -outlined by the cystic duct, right liver lobe, and the common hepatic duct-, which indicates the importance of a clear anatomical demonstration of the cystic duct and cystic artery to perform a safe cholecystectomy (5).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Laparoscopic cholecystectomy (LC) has become the gold standard for the surgical treatment of benign gallbladder diseases owing to its shorter hospitalization, more rapid recovery, and much fewer wound complications when compared to open cholecystectomy (1)(2)(3)(4). However, a direct vision is essential for safe dissection of Calot's triangle -outlined by the cystic duct, right liver lobe, and the common hepatic duct-, which indicates the importance of a clear anatomical demonstration of the cystic duct and cystic artery to perform a safe cholecystectomy (5).…”
Section: Introductionmentioning
confidence: 99%
“…Several reports suggested that postoperative hospital stay was significantly shorter in LC series when compared with CC series (2,4,22,(42)(43)(44). Ivatury et al (45) concluded that postoperative stay after LC was associated with ASA score.…”
mentioning
confidence: 99%
“…Jatzko G R, (21) Orlando et al (22) and Daniel J et al (4) reported an overall complication rate of 1.5%, 8.6% and 2% respectively in their studies on laparoscopic cholecystectomy. Jatzko and others in their study have observed that the main detrimental factors relating to overall complications are open cholecystectomy for Grade 1 complication, old age and acute cholecystitis for Grade 2a complication and old age, acute cholecystitis and length of operation for Grade 2b complications.…”
Section: Of 400 Cases Taken Up For Laparoscopic Cholecystectomy 30mentioning
confidence: 97%
“…Jatzko and others in their study have observed that the main detrimental factors relating to overall complications are open cholecystectomy for Grade 1 complication, old age and acute cholecystitis for Grade 2a complication and old age, acute cholecystitis and length of operation for Grade 2b complications. (21) In their study on laparoscopic cholecystectomy Cusheri et al, (20,10) Orlando et al (22) and Paulino Netto (9) reported mortality rate of 0.3% each, Deziel et al (22) of 0.04%, while no mortality was reported by Rubio, Voyles et al, Flower et al and Dubois F. (8,23,24) In the end, we might assume that introduction of LC, a new surgical method for treatment of patients with cholelithiasis was adopted due to its great advantages for the patients and hence can be defined as the 'New Gold Standard' for their treatment. A number of problems still under discussion as well as the negative views of the supporters of conventional methods should not discourage us to continue our efforts and research in this field.…”
Section: Of 400 Cases Taken Up For Laparoscopic Cholecystectomy 30mentioning
confidence: 99%
“…At the time of the repair, the most serious problem is the injury to the main bile duct. Although the differences are not statistically significant, this injury is more frequently seen in laparoscopic cholecystectomy (1 % of cases) [13][14][15][16]. In open cholecystectomy in the operation of portocaval anastomosis, the portal vein is mobilized circumferentially at its midpoint [17].…”
Section: Measurement Of the Celiac Trunk Diametermentioning
confidence: 99%